2022
DOI: 10.1007/s10603-022-09524-5
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Corridors and the Case of Meat

Abstract: Consumer policy must address the unsustainability of consumption which now threatens consumer safety in the form of the climate and ecological crises. Arguably, only strong sustainable consumption governance methods can bring about changes at the scale and speed required. This article discusses one emerging policy tool within strong governance, namely consumption corridors which could bring about absolute reductions in the negative impacts of consumption in a just manner and using deliberative democracy. Consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…A transition to consider meat alternatives offers new interest on vegetables and grains (Holm & Møhl, 2000). Several studies reported meat reducers (flexitarian and plantarian) and meat avoiders (vegetarians and vegans) (Kanerva, 2013;Possidónio et al, 2021). For example, 37% of consumers in Finland consume beef, and there are no consumptions of insect-or plantbased protein products (Niva & Vainio, 2021).…”
Section: Consumers Perceptions To Insect- Seaweed-and Plant-based Pro...mentioning
confidence: 99%
“…A transition to consider meat alternatives offers new interest on vegetables and grains (Holm & Møhl, 2000). Several studies reported meat reducers (flexitarian and plantarian) and meat avoiders (vegetarians and vegans) (Kanerva, 2013;Possidónio et al, 2021). For example, 37% of consumers in Finland consume beef, and there are no consumptions of insect-or plantbased protein products (Niva & Vainio, 2021).…”
Section: Consumers Perceptions To Insect- Seaweed-and Plant-based Pro...mentioning
confidence: 99%
“…The optimal space should allow 'everybody to satisfy their needs without compromising others' ability to meet their own' [211, p 1]. Consumption corridors are typically negotiated using deliberative democracy processes [211,212]. They offer potential as strong governance tools that can place caps on consumption that can 'bring about absolute reductions in the negative impacts of consumption in a just manner' [212, p 619].…”
Section: Pathways To Redistributionmentioning
confidence: 99%
“…Consumption corridors (CCs) constitute an innovative approach that is gaining traction in the literature on sustainable consumption governance (Fuchs 2020;Fuchs et al 2021;Sahakian et al 2021). At the general conceptual level, Kanerva (2022) introduces the idea of using CCs for the case of meat.…”
Section: Applying the Concept Of Corridors Of Sustainable Consumptionmentioning
confidence: 99%
“…At the individual level, meat consumption is not just a satisfier for nutrition but also fulfills other needs such as identity or social belonging (Kanerva 2022;Nguyen and Platow 2021). Including such considerations when defining the floor of the meat CC would make the calculations far more complex.…”
Section: Acknowledging Cultural Acceptability and Other Intangible Hu...mentioning
confidence: 99%